A Study on Green Product Purchase among Internet Generation in Malaysia - Lee, Ailing (2012)
Environmental degradation issues such as global warming have brought the message to the internet generation that their purchasing power can cause a huge impact on the environment. The purpose of this research is to determine the key factors that affect the internet generation to be green product purchases. This research is based on the quantitative research approach. The author conducted a survey through 400 questionnaires and only 375 are valid respondents. The survey is this research got feedback from the internet generation (18-34 years old) who are green product purchasers. The factors for the internet generation to be green product purchasers will be analyzed from different perspective, and will revolve around the literature review. Four components of green product purchases will be measured such as Eco literacy, marketers’ eco-label, environmental advertising and price and quality perception. In this research, statistical analysis was used in the descriptive analysis, reliability analysis, factor analysis and multiple regression analysis to serve as a guideline for the marketers to improve that marketing strategies. The thesis concludes with a discussion of the results, which include the recommendations of the findings, recommendations for future research and personal reflection.